Harmony In the Classroom: Integrating the Values of Appreciation and Empathy Through Learning and The Anti-Bullying Campaign in Schools - Alhamuddin; Fahmi Fatwa Rosyadi Satria Hamdani (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research aimed to analyse the integration of respect and empathy values in the context of learning, focusing on the purpose, implementation, evaluation, and supporting and inhibiting factors. The main objective of this research is to explore the understanding of how the values of respect and empathy can be effectively integrated in the learning process to shape students' character. The implementation of respect and empathy values is done through embedding character education in the curriculum, teacher training that focuses on character teaching strategies, and the application of teacher behaviour models as positive examples. Evaluation is done by including character assessment in student assessments, both formative and summative. Supporting factors in this integration involve student participation in decision-making, an effective guidance and counselling programme and parental involvement in supporting character learning at home. However, a number of inhibiting factors were also identified, including high curriculum demands, inequality and discrimination, and lack of teacher and student awareness of the importance of character values.  Suggestions and recommendations resulting from this research involve the need for changes to the curriculum by adding specific modules or subjects that emphasise character values. Continuous teacher training needs to be strengthened, and parent and student engagement approaches should be improved. Evaluation should be more balanced, including character aspects in student assessment. The implementation of inclusive and democratic strategies needs to be improved to ensure that every student feels the positive impact of integrating the values of respect and empathy. Thus, it is hoped that the results of this study can provide practical guidance for schools in their efforts to shape students' character through the integration of respect and empathy values in learning.